Enhancement of Sensory Quality, Nutritional And Health Benefits of Complementary Baby Food Through 2–6µm Mid-Infrared Irradiation (Global Journal of Medical Research, 2024)
Complementary foods are provided to infants when the amount of breast milk produced by the mother is insufficient Numerous baby foods are available in the market worldwide but their quality is questionable Therefore we used our recently invented 2 6 m midinfrared generating atomizer MIRGA on various brands of complementary baby foods to safely enhance their quality in terms of nutrition and sensory attributes The effects of mid-IR irradiation on baby food included compound transformation changes in the protein concentration changes in the chemical bond and changes in the nanoparticle morphology The matrix structure and sensory attributes and other benefits were analyzed and validated with various tests and are presented here
Keywords: MIRGA; 2–6μm mid-infrared; complementary infant food; quality enhancement; food safety; economy